Thermal evaluation of laminated composite phase change material gypsum board under dynamic conditions - Zhou, Tongyu; Darkwa, Jo; Kokogiannakis, Georgios (Elsevier, 2015)
Thermal evaluation of non-deform laminated composite phase change material (PCM) gypsum board has been carried out. The theoretical studies covered the analysis of different thicknesses of PCM layers and their corresponding heat transfer rates during energy storage and discharge processes. A simply approach was also provided for determining the appropriate thicknesses of PCM layer under various conditions. For the purpose of experimental study and validation, a laminated gypsum board consisting of a 4 mm PCM layer was evaluated in a naturally ventilated condition. It achieved a maximum heat exchange of 15.6 W/m2 and a maximum energy storage of 363.7 kJ/m2. A model room built with the laminated PCM gypsum boards was also evaluated and achieved a maximum temperature reduction of 5 °C as compared with 1.8 °C for the one with ordinary gypsum board. Even though about 25% of the energy stored could not be released within the targeted period, the overall thermal performance of the PCM gypsum board was quite remarkable. Further heat transfer enhancement mechanism may therefore be necessary for the energy discharge process.